Analysis Of Brand Communication Strategies Of Chinese Brands In Kyrgyzstan Market (Architecture Image Studies, 2025)
This paper focuses on the localized communication practices of Chinese brands in the Kyrgyz market, and selects four typical cases in the fields of home appliances, telecommunications, FMCG and building materials for a cross-industry comparative study. The study finds that, in terms of branding, Chinese companies have innovatively adopted a triple positioning strategy: opening up market gaps with "high cost performance", building competitive barriers with "technological advantages + localized services", and establishing emotional ties through "cultural empathy", which has successfully enhanced both brand recognition and reputation. Specifically for communication practice, the enterprise adopts the combination strategy of traditional media and digital communication - TV ads to strengthen the brand's sound volume, social media to deepen user interaction, and outdoor scenario-based marketing to trigger instant consumption, forming a three-dimensional communication network. It is worth noting that the creative transformation of local cultural symbols in the narrative text makes the communication content more emotionally penetrating. The study further reveals that public relations and social responsibility investment constitute key dimensions of brand soft power cultivation. Through government relations, media cooperation and community welfare programs, Chinese companies have effectively created an image of responsible corporate citizenship. In terms of digital transformation, the establishment of a multilingual communication matrix has not only improved the efficiency of information reach, but also reconstructed the consumer journey through the OMO model of online-offline integration. According to the data, brands adopting the four dimensions of precise market segmentation, product portfolio optimization, channel diversification and customized promotional strategies have increased their customer retention rate by 37% on average. This paper innovatively proposes a trinity theoretical model of "strategic synergy-cultural adaptation-digital empowerment", which provides a new analytical framework for brand communication research in emerging markets. Empirical evidence shows that the model is highly applicable to explaining the effectiveness of multinational brands' localized communication, especially in the optimization of channel strategy and social media operation, which is of great practical value